2020
DOI: 10.1111/ele.13463
|View full text |Cite
|
Sign up to set email alerts
|

Testing for deterministic succession in metazoan parasite communities of marine fish

Abstract: Parasite communities are similar to free‐living communities; decay of similarity over geographic distance, theory of island biogeography, species–area relationships and nestedness have been documented in both communities. Ecological succession has been studied in free‐living communities but has rarely been examined in parasite communities. We use seriation with replication to test the hypothesis that succession of parasite community structure is deterministic, thus developing throughout consecutive changes alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
0
3
0
1
Order By: Relevance
“…However, it has been recently shown that α TD of parasite communities is determined by host age-class like an ecological succession of communities of free-living organisms. Thus, if hosts of different age-classes were analysed together it could mask an actual deterministic pattern of parasite community assemblage (Espínola-Novelo et al, 2020). Nonetheless, we consider that this is not a likely scenario in this study since parasite communities were mainly sampled from fish of two consecutive age-classes out of nine (classes 3 and 4 according to those described for M. cephalus in Espínola-Novelo et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been recently shown that α TD of parasite communities is determined by host age-class like an ecological succession of communities of free-living organisms. Thus, if hosts of different age-classes were analysed together it could mask an actual deterministic pattern of parasite community assemblage (Espínola-Novelo et al, 2020). Nonetheless, we consider that this is not a likely scenario in this study since parasite communities were mainly sampled from fish of two consecutive age-classes out of nine (classes 3 and 4 according to those described for M. cephalus in Espínola-Novelo et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the fish sampled during the two sample times were possibly a heterogeneous group of ages (1 to 3 years) with lengths ranging from 20 to 30 cm according to those reported by Knaggs & Parrish (1973) and Schaefer (1980) . Espínola-Novelo et al . 2020 indicated that a seriated pattern of succession was detected in host species with a higher number of age-classes, which increased the probability of obtaining a more accurate estimate of the total number of parasite species that one host species can harbor along their ontogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Este es el primer estudio de aspecto ecológico en la fauna parasitaria de H. peruanus. Finalmente, los autores incentivan a seguir aportando con estudios ecológicos de la fauna parasitaria de H. peruanus para determinar si las poblaciones de parásitos tienden a una sucesión secuencial a lo largo del tiempo o una sucesión aleatoria (38).…”
Section: Discussionunclassified